2019
DOI: 10.1038/s41467-019-09006-2
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 genome editing induces megabase-scale chromosomal truncations

Abstract: CRISPR-Cas9 is a promising technology for genome editing. Here we use Cas9 nuclease-induced double-strand break DNA (DSB) at the UROS locus to model and correct congenital erythropoietic porphyria. We demonstrate that homology-directed repair is rare compared with NHEJ pathway leading to on-target indels and causing unwanted dysfunctional protein. Moreover, we describe unexpected chromosomal truncations resulting from only one Cas9 nuclease-induced DSB in cell lines and primary cells by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
256
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(285 citation statements)
references
References 65 publications
9
256
0
Order By: Relevance
“…However, larger than expected deletions that are suggested by our FISH results ( Fig. S6) and others' reports [32][33][34] , would be missed. Although a single ddXR assay cannot measure all possible excision sizes and rearrangements, further adjustments, similar to the inversion assay, can be easily designed to quantify specific rearrangements of interest once they are defined.…”
Section: Discussionsupporting
confidence: 43%
“…However, larger than expected deletions that are suggested by our FISH results ( Fig. S6) and others' reports [32][33][34] , would be missed. Although a single ddXR assay cannot measure all possible excision sizes and rearrangements, further adjustments, similar to the inversion assay, can be easily designed to quantify specific rearrangements of interest once they are defined.…”
Section: Discussionsupporting
confidence: 43%
“…Beyond its impact on biological research, CRISPR-based approaches have been considered for various applications in medicine, from reparative editing of primary cells to the development of new strategies for treating a variety of genetic diseases, including cancer. However, several clinical trials based on CRISPR technology have been deferred due to significant potential risks, including off-target effects 2,3,4 , generation of unexpected chromosomal alterations 5 and potential immunogenicity 6 . Other studies have demonstrated that double stranded breaks (DSBs) induced by CRISPR-Cas9 during gene knockout (KO) can lead to DNA damage response, whose level is associated with the copy number of the targeted gene.…”
mentioning
confidence: 99%
“…Successful G1-variant knock-in and cassette removal were confirmed by Sanger sequencing (Figure 1A, Figure S1A-C). Because CRISPR-mediated genome editing can occasionally induce chromosomal changes 22 , we verified that our genome-edited iPSCs maintained a normal karyotype (Figure S1D-E).…”
Section: Resultsmentioning
confidence: 79%